Determinants of cigarette consumption among Indonesian adolescents: a cross-sectional study - Halid, Musparlin; Amaliah, Lili; Nurcahyati, Sri; Jayanti, Krisnita Dwi; Supriatin, Supriatin; Suyitno, Suyitno; Maretalinia, Maretalinia (International Journal of Public Health Science (IJPHS), 2025)
Adolescent smokers in Indonesia remain a problem that impacts educational output. This study aimed to examine the determinants of cigarette consumption among school-age adolescents. The study employed a cross-sectional design in Lombok Island, West Nusa Tenggara Province, Indonesia. The study collected data from January 2022 to July 2023. The total sample in this study consisted of 819 adolescents from junior high and senior high schools (SHS). Among all respondents, 438 adolescents (53.5%) reported smoking >10 stems/day. The binary logistic regression results revealed that significant variables associated with cigarette consumption included males aged 14 to 16, who drank alcohol more than three times a week, consumed more than three liters of alcohol a week, had low parental education levels, had peer influence, were exposed to social media, had parents who smoked, and had experienced parental divorce. The collaboration between stakeholders at the school level and parents, such as counseling and supervision intensive, can prevent adolescent smoking behavior.